PERAMALAN PRODUKSI TEH HIJAU DENGAN PENDEKATAN AUTOREGRESSIVE INTEGRATED MOVING AVERAGE - Wijaksono, Satrio; Sulistijanti, Wellie (Universitas Muhammadiyah Semarang, 2017)
Tea plantation is one aspect of the lucrative agricultural sector in Indonesia.The world's need for very large plantation commodities, especially tea. theproduction of tea shoots as a raw material greatly determines the continuity oftea production as a whole. Tea production usually fluctuates from time to time.To establish a management view of future tea productivity forecasting, we canuse the Autoregressive Integrated Moving Average (Time Series) AutoregressiveIntegrated Moving Average (ARIMA) analysis. With the MSE value of 0.03668the best ARIMA model obtained is ARIMA (1.0.0), with general forecastingmodel: The data used is the production data of tea sales at PT. Rumpun Sari Medini from 2011-2016. The purpose of this research is to predict the amount of teasales production at PT. Rumpun Sari Medini Year 2017. Based on the results ofthis study, it was found that the highest tea production value occurred inDecember 2017 of 226,670 quintals, while the lowest production in January2017 was 226,603 quintals.Keyword: ARIMA, Peramalan Produksi Teh, PT. Rumpun Sari Medini